Decision-making application Implementation to Determine the Location of an Android-Based Football Watching Café in DKI Jakarta - Elis Sondang Dasawaty; Prima Apriwenni; Naufal Naufal; Budi Wasito; Akhmad Budi (International Journal of Artificial Intelligence Research, 2022)
As more and more levels of the technology that can help us on any side, we must use this advantage as good as possible. This led us to produce more applications to make a better living for human races. So is the growth of the football fans community. But on the other hand, there are no application that exclusively provides information systems with location- specific services for football fans to do match screening.To establish a Decision Support System  with  location-based  services,  the  author  uses  a variety  of theories  used  as  a references. Theories are information systems, databases, SQL, Java programming languages, PHP Programming languages, Android Operating System, Decision Making and Location Based Service. The application is developed with the Java-based Java programming language that can be easily accessed and run through the internet. In this research, data collection is done by doing direct observation with the culture of match screening. The system development is done using object-oriented analysis and design that can be described with Unified Modeling Language (UML).The results of this research is a Decision Making application that can be used by anyone, especially for those who are fans of football clubs and cafe owners with the match screening facility . With its uniqueness, this is can be an attraction for cafe owners who want to promote their cafe. The conclusion of this research is the application of decision making can be used as media to publish cafe with match screening facility and information of match that aired, so it can facilitate the spectators of soccer sport in order to funnel their hobby.